Spatial and Temporal Aspects of Fungicide Resistance in Venturia inaequalis (Apple Scab) Populations in Northern Germany - Roland W. S. Weber; Rebekka Busch; Johanna Wesche (BioTech)
Venturia inaequalis, the cause of apple scab, readily develops resistance to fungicides with specific modes of action. Knowledge of the spatial and temporal pattern of resistance development is therefore relevant to fruit producers and their consultants. In the Lower Elbe region of Northern Germany, a two-year survey based on a conidial germination test was conducted, examining fungicide resistance in 35 orchards under Integrated Pest Management (IPM), 16 orchards of susceptible cultivars as well as a further 12 orchards of scab-resistant (Vf) cultivars under organic management, and 34 abandoned or unmanaged sites. No evidence of resistance to SDHI compounds (fluopyram, fluxapyroxad) was found after >5 yr of their regular use. Resistance to anilinopyrimidines (cyprodinil, pyrimethanil) had disappeared 15 yr after its widespread occurrence. Isolates from a few IPM orchards showed a reduced sensitivity to dodine. Double resistance to the MBC compound thiophanate-methyl and the QoI trifloxystrobin was rare in V. inaequalis strains that had achieved breakage of Vf-resistance, but very common (>50%) on scab-susceptible cultivars in IPM, organic and abandoned orchards in the ‘Altes Land’ core area of the Lower Elbe region, and in IPM orchards in the periphery. We conclude that resistance to QoI and MBC fungicides is persistent even decades after their last use, and that the core area harbours a uniform population adapted to intensive crop protection, whereas isolated orchards in the periphery are colonised by discrete populations of V. inaequalis.